Outsourcing jako przejaw innowacyjności w zarządzaniu podmiotami branży hotelarskiej - Jaremen, Daria Elżbieta (Outsourcing as an Innovation in the Hotel Management, 2008)
The aim of this paper is to describe the practical using of the conception of outsourcing in hotel industry. The author defines the category of outsourcing. The review of the literature of outsourcing and the presentation knowledge gained during the author's own research allows to describe the role of outsourcing in hotel industry. The article identifies the functions, which are outsourced, the advantages and results of using outsourcing by hotels. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 138-145